Vitamin E does not decrease the incidence of chemotherapy-induced peripheral neuropathy: a meta-analysis - Huang, Huaping; He, Mei; Liu, Lihua; Huang, Lili (Contemporary Oncology/Współczesna Onkologia, 2016)
Aim of this study : Chemotherapy-induced peripheral neuropathy (CIPN) is a major complication of cancer patients with chemotherapy. Although many interventions have been evaluated in previous studies, findings are controversial. The aim of this meta-analysis is to assess the efficacy of vitamin E supplementation in preventing CIPN. Material and methods : The electronic databases MEDLINE, EMBASE, and the Cochrane Central Register of Controlled Trials were systematically searched from their inception to December 31, 2013 to identify relevant randomised controlled trials. Two reviewers independently scanned and extracted the data of included studies. Review Manager 5.2 was used to analyse data. Results : Six articles involving 353 patients were included in meta-analysis. The results showed that vitamin E supplementation did not appear to significantly decrease the incidence of CIPN (relative risk (RR), 0.55; 95% confidence interval (CI), 0.29 to 1.05; p = 0.07), with significant heterogeneity (I2 = 77%). However, Vitamin E supplementation can significantly prevent cisplatin associated neurotoxicity (RR, 0.31; 95%CI, 0.17 to 0.58; p = 0.0002), with no heterogeneity (I2 = 0%). Conclusions : Vitamin E administration dose not decrease the incidence of CIPN. However, additional randomised controlled trials using large samples are needed to confirm the role of vitamin E supplementation.